2017
DOI: 10.1152/ajpregu.00385.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation and regional cerebral perfusion responses with resistance breathing during central hypovolemia

Abstract: Resistance breathing improves tolerance to central hypovolemia induced by lower body negative pressure (LBNP), but this is not related to protection of anterior cerebral blood flow [indexed by mean middle cerebral artery velocity (MCAv)]. We hypothesized that inspiratory resistance breathing improves tolerance to central hypovolemia by maintaining cerebral oxygenation (ScO), and protecting cerebral blood flow in the posterior cerebral circulation [indexed by posterior cerebral artery velocity (PCAv)]. Eight su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…preserved central blood volume, enhanced venous return, improved cardiac filling and/or maintained cerebral perfusion) are responsible for the ITD‐induced improvements in tolerance need to be investigated further. Furthermore, on the account of the expanding body of evidence suggesting that cerebral hypoperfusion does not play as pivotal of a role in the tolerance to central hypovolaemia (Ainslie, Hoiland, & Bailey, ; Jeong, Shibata, Levine, & Zhang, ; Kay et al., ; Lucas et al., ; Lucas, Pearson, Schlader, & Crandall, ) as previously thought, future research directed at elucidating the specific physiological processes that improve tolerance to haemorrhage during heat stress is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…preserved central blood volume, enhanced venous return, improved cardiac filling and/or maintained cerebral perfusion) are responsible for the ITD‐induced improvements in tolerance need to be investigated further. Furthermore, on the account of the expanding body of evidence suggesting that cerebral hypoperfusion does not play as pivotal of a role in the tolerance to central hypovolaemia (Ainslie, Hoiland, & Bailey, ; Jeong, Shibata, Levine, & Zhang, ; Kay et al., ; Lucas et al., ; Lucas, Pearson, Schlader, & Crandall, ) as previously thought, future research directed at elucidating the specific physiological processes that improve tolerance to haemorrhage during heat stress is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In a normothermic state, the ITD improves tolerance to a simulated haemorrhagic challenge (Kay, Sprick, & Rickards, ; Rickards, Ryan, Cooke, Lurie, & Convertino, ). In swine, the ITD is effective in the rescue of hypotension resulting from heat stroke (Voelckel, Yannopoulos, Zielinski, McKnite, & Lurie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Syncope is associated with a decrease in cerebral blood velocity (CBV), often monitored in middle cerebral arteries (MCA) (Kay, Sprick, & Rickards, 2017;Schondorf, Benoit, & Stein, 2001;van Lieshout, Wieling, Karemaker, & Secher, 2003). However, both MCAs supply the anterior part of the brain and questions arise as to whether the posterior irrigation could rather be linked to the appearance of pre-syncopal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of orthostatic symptoms (such as dizziness, nausea and blurred vision) could therefore refer to posterior cerebral hypoperfusion, notably in posterior cerebral arteries (PCA). Kay & Rickards (2016) demonstrated that individuals with low tolerance to orthostatic stimulation show greater decrease in PCA mean blood velocity (PCAvmean) during a progressive lower body negative pressure protocol where tolerance was evaluated as the onset of presyncope/appearance of symptoms (Kay et al, 2017). Conversely, these investigators did not report any differences in MCA mean blood velocity (MCAvmean) changes during the protocol compared to baseline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation